THE CONCEPT OF JURISDICTION IN THE AIR: TO WHAT EXTENT CAN IT BE UPHELD AGAINST UNRULY PASSENGERS IN INTERNATIONAL AIR TRANSPORT? - Nova Maulani; Shannon Suryaatmadja (Padjadjaran Journal of International Law, 2021)
ABSTRACT Jurisdiction is essential for statehood along with the right to prescribe and enforce laws. Unruly behaviour may threaten air transportation security and safety, including the passenger safety, disrupts other passengers and crew causing delays and diversions. But due to loopholes on the existing laws, and lack of choice of jurisdiction, such offenses often remain unpunished. This article aims to seek the best role that Indonesia should take to implement its jurisdiction on aircrafts in international flights and to protect its citizens in international flight. It provides an overview and analysis of existing international and Indonesian legal instruments in handling unruly passengers and to support extended jurisdiction choices so unruly passengers and other related criminal activities can be regulated and punished as necessary to ensure the safety and security, including the Chicago Convention 1944 and the Annex 17 on Security, The Tokyo Convention 1963 and the Montreal Protocol 2014. Keywords: Air Law, Aviation, Aviation Security, Jurisdiction, Unruly Passengers ABSTRAK Esensi dari yurisdiksi penting bagi negara dalam menjalankan dan menegakan hukum. Perilaku tidak tertib dapat mengancam keamanan dan keselamatan transportasi udara, dimana di dalamnya terdapat unsur keselamatan penumpang, gangguan terhadap awak dan penumpang lainnya, serta dapat mengakibatkan keterlambatan dan diversi. Namun demikian, dengan adanya celah dalam hukum dan peraturan, serta minimnya pilihan yurisdiksi, tindakan tersebut sering tidak dikenakan hukuman. Artikel ini bertujuan mencari peran terbaik yang harus diambil Indonesia, dalam mengimplementasi yurisdiksinya di pesawat dan melindungi warga negaranya dalam penerbangan internasional. Artikel ini memberikan tinjauan umum dan analisis instrumen hukum Internasional dan hukum Indonesia yang menangani penumpang yang sulit diatur, termasuk di dalamnya Konvensi Chicago 1944 dan Annex 17 tentang Keamanan,Konvensi Tokyo 1963 dan Protokol Montreal 2014 . Kata Kunci: Aviasi, Hukum Udara, Keamanan Penerbangan, Penumpang yang Sulit Diatur, Yurisdiksi